2015
DOI: 10.1080/19440049.2015.1101494
|View full text |Cite
|
Sign up to set email alerts
|

Culture and molecular identification of fungal contaminants in edible bird nests

Abstract: Widespread food poisoning due to microbial contamination has been a major concern for the food industry, consumers and governing authorities. This study is designed to determine the levels of fungal contamination in edible bird nests (EBNs) using culture and molecular techniques. Raw EBNs were collected from five house farms, and commercial EBNs were purchased from five Chinese traditional medicine shops (companies A-E) in Peninsular Malaysia. The fungal contents in the raw and commercial EBNs, and boiled and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 30 publications
3
14
0
Order By: Relevance
“…Before the radiation, RC EBNs readings exceeded the permittable limit set by Standard Malaysia. Similarly, as reported by Chen et al (2015), all EBNs had fungal CFU that exceeded the limit (100 CFU/g). However, when RUC EBNs and RC EBNs were compared, there were no significant difference found between the total number of bacteria and fungi in both the samples but they did show significant difference in types of isolates (Chen et al, 2015;Wong S. F. et al, 2018).…”
Section: Bacterial Fungi and Mites In Ebnssupporting
confidence: 80%
See 1 more Smart Citation
“…Before the radiation, RC EBNs readings exceeded the permittable limit set by Standard Malaysia. Similarly, as reported by Chen et al (2015), all EBNs had fungal CFU that exceeded the limit (100 CFU/g). However, when RUC EBNs and RC EBNs were compared, there were no significant difference found between the total number of bacteria and fungi in both the samples but they did show significant difference in types of isolates (Chen et al, 2015;Wong S. F. et al, 2018).…”
Section: Bacterial Fungi and Mites In Ebnssupporting
confidence: 80%
“…Similarly, as reported by Chen et al (2015), all EBNs had fungal CFU that exceeded the limit (100 CFU/g). However, when RUC EBNs and RC EBNs were compared, there were no significant difference found between the total number of bacteria and fungi in both the samples but they did show significant difference in types of isolates (Chen et al, 2015;Wong S. F. et al, 2018). Wong S. F. et al (2018) reported that Enterobacter, Exiguobacterium, Brevibacillus, Caryphanon, and Solibacillus species were found exclusively in the commercial EBNs.…”
Section: Bacterial Fungi and Mites In Ebnssupporting
confidence: 80%
“…Some species of subgenus Polypaecilum seem to be associated with birds; for example, the isolations of A. atacamensis from cave soil beneath an ancient guano deposit in the Chilean Atacama Desert and A. insolitus from chicken litter ( Riegel et al., 1996 , Martinelli et al., 2017 ). Chen et al. (2015) reported an unidentified species of subgenus Polypaecilum (“ Phialosimplex sp.”) isolated from edible bird nests in Malaysia using Sabouraud dextrose agar.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, yeast content for all EBN samples was within the tolerance level. A study done found that the amount of yeast and mould had exceeded the limit set by SIRIM for all EBN [11]. e common fungi that isolated were Aspergillus sp., Candida sp., Cladosporium sp., Neurospora sp., and Penicillium sp.…”
Section: Safety Profile: Microbiology Profilementioning
confidence: 98%
“…Moreover, the analyses previously performed were not representative of all regions in Malaysia [3,4,7]. Despite being acclaimed as a nutritious food, there are many safety issues arising from Malaysia EBN in recent years; namely, high nitrate and nitrite contents [8,9], EBN adulteration [5], presence of heavy metal [4,10], pathological microorganism, and fungal infection [11]. e contaminants in EBN may be potentially harmful to the consumers.…”
Section: Introductionmentioning
confidence: 99%